Pembinaan Masyarakat Islam Melalui Pendekatan Dzikir dan Pikir Studi Pada Majlis Ta’lim Ar-Rahman RT 17 Desa Way Huwi Kecamatan Jatiagung Lampung Selatan - AD, Yahya (Universitas Islam Negeri Raden Intan Lampung, 2017)
Based on the National Survey of BNPT November 2017, the potential for radicalism in Lampung Province reached 58.38%. The increasingly widespread days of violence, both in the household and community, whether on a small scale or a particular community, or large scale such as between villages, between villages, even between sub-districts involving ethnic and religious elements. Majlis Ta'lim Ar-Rahman in the guidance of the community in RT. 17 Village Way Huwi District Jatiagung Lampung Selatan interesting to investigate, because the coaching system that combines the development of thought and dhikr. The development of thought aspect through the study of Islamic material systematically according to its scope, then applied it through amaliah dhikr by tasawuf-tarekat method. To describe how the implementation of coaching is applied and what kind of picture of religious experience experienced by members or jama'ahnya then this study using the approach of Islamic sciences and psychology, especially Islamic psychology (Sufi psychology), with descriptive qualitative method. Based on in-depth interviews with participant observation it can be concluded that coaching through dhikr approach and thought is able to develop society toward religious transformation.